Effect of Hemoglobin Levels Pregnant Women on the Predictive Value for Preeclampsia of ROT (Roll-Over Test) - Nina Hidayatunnikmah; Tetty Rihardini (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2020)
Preeclampsia is a medical condition which accounts for the global incidence of maternal mortality of 76,000/year and infant mortality of 500,000/year. Early preventive action is a critical dimension to reduce the risk to the mother and the fetus. Roll Over Test (ROT) is one of the predictors of preeclampsia conducted in the 2nd trimester. High hemoglobin levels in pregnant women can lead to pregnancy hypertension, which can potentially lead to preeclampsia. This study aims to analyze the effect of hemoglobin levels on the predictive value for preeclampsia of ROT (Roll Over Test) among pregnant women. The benefits of this study are to get preventive method updates to decrease the incidence of preeclampsia in pregnant women as early as possible and to review the policy of giving Fe to all pregnant women from the 1st trimester to the 3rd trimester. The study was conducted for three months in the work area of Siwalankerto Community Health Center, Surabaya. Data on hemoglobin levels were obtained from the MCH booklet for pregnant women. ROT's preeclampsia's predictive value was obtained by checking supine values and left lateral blood pressure among 30 pregnant women. A statistical test was performed using a logistic regression test. Based on 30 samples of pregnant women, the results showed that 16 pregnant women had hemoglobin levels of >13gr/dl (53.3%), and 14 pregnant women (46.7%) had a positive predictive value of ROT. The effect test analysis results showed a positive relationship between hemoglobin levels and the predictive value for preeclampsia (p=0.04, B=1.299). Thus, pregnant women who experienced an increase in the hemoglobin levels of 1 g/dl had a potential of 1.299 times to have a positive ROT value.